2022
DOI: 10.3389/fvets.2022.921481
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Vectored African Swine Fever Virus pp220 Induces Robust Antibody, IFN-γ, and CTL Responses in Pigs

Abstract: African Swine Fever Virus (ASFV) poses a serious threat to the pork industry worldwide; however, there is no safe vaccine or treatment available. The development of an efficacious subunit vaccine will require the identification of protective antigens. The ASFV pp220 polyprotein is essential for virus structural integrity. This polyprotein is processed to generate p5, p34, p14, p37, and p150 individual proteins. Immunization of pigs with a cocktail of adenoviruses expressing the proteins induced significant IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 91 publications
1
9
0
Order By: Relevance
“…As there is no effective vaccine or treatment for ASFV, it is required to identify protective antigens. ASFV pp220 polyprotein essential for virus structural integrity [27] was found containing epitopes that can induce robust immune responses in pigs, suggesting it will be promising candidate in vaccine development [27].…”
Section: Resultsmentioning
confidence: 99%
“…As there is no effective vaccine or treatment for ASFV, it is required to identify protective antigens. ASFV pp220 polyprotein essential for virus structural integrity [27] was found containing epitopes that can induce robust immune responses in pigs, suggesting it will be promising candidate in vaccine development [27].…”
Section: Resultsmentioning
confidence: 99%
“…However, the results revealed that a greater number of epitopes from other protein sources exhibited higher immunogenicity than epitopes found on these structural proteins. Four out of the ten protein sources of the T-cell epitopes in the study, including polyprotein pp220 (CP2475L) 27 , 71 , 72 , guanylyltransferase (NP868R) 22 , helicase/primase (F1055L) 72 , and MGF 360-11L 20 , 72 , induced T-cell responses against ASFV in in vitro experiments. Meanwhile, all four protein sources of the LBL epitopes—minor capsid protein p49 (B438L) 73 , envelope protein p22 22 , 74 , transmembrane protein (C257) 22 , and major capsid protein p72 (B646L) 22 , 73 76 have shown positive antibody response against the virus in in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…pp220 polyprotein contains at least four T cell epitopes, which are located at position 161–169, 859–867, 1363–1371 and 1463–1471. Strong IFN-γ responses can be induced in domestic pigs by immunization with pp220 ( Zajac et al, 2022 ). Previous studies have predicted that epitopes IADAINQEF, QIYKTLLEY and SLYPTQFDY (located in pp220) were highly conserved T cell epitopes in ASFV genome and could therefore be a promising candidate for vaccine development ( Herrera and Bisa, 2021 ).…”
Section: The Major Structural Proteins In Asfv Vaccine Developmentmentioning
confidence: 99%